La turbera del Río Silencio (El Cairo, Siquirres, Costa Rica): paleoambientes lagunares influenciados por las cenizas del volcán Turrialba - Obando, Luis Gmo. (2011)
The peat deposit of Rio Silencio have an abnormal thickness (a maximum of 14 m) for the peat deposits of Costa Rica. In the 8 wells, the vegetation rests are predominantly woody and ferny. Our study, showed at least 3 flora-cycles development interrupted by clay beds of cineritic origin between them. The woody flora decrease and the ferns are dominant, which suggest the enviroment destruction caused by volanic ash fall. The well correlations show a complicated paleo-environment with isolated ponds and alluvial influence. The peat accumulation rate was 1 m each 650-850 years. The geographic and temporal correlations show that the ash bed-clays are the result of great eruptions of the Turrialba Volcano (35 km to the SW) 2000 and 3370 years before present. The volcanic ash was probably carried towards to NE of Costa Rica by high winds during the dry periods.